DEVELOPING A POP-UP BOOK TO TEACH WILD ANIMALS IN ENGLISH FOR KINDERGARTEN AT TK AL HIDAYAH TANGGUNG - Imroatu Sholihah; Siti Rofi’ah; Istina Atul Makrifah; Khristin Sri Utami Nardiyana (IKIP Siliwangi, 2023)
Children learn many things in Kindergarten, including language learning. One of the languages they learn in Kindergarten is English. The teacher and students are needing some appropriate media to deliver materials, such as the pop-up book. This research is Research and Development (R&D) with using the ADDIE model. The data in this research are collected through interviews, observation, questionnaires, and student test results. The validation from the media expert resulted in 92,5%, while the validation from the material expert resulted in 95%. There were enhancements in the student's test results, from 37,86% (when pre-test) to 82,86% (when post-test). The result conveyed that there was an improvement in English learning by using the pop-up book. The pop-up book can be an appropriate media to teach English in Kindergarten. Keywords: Pop-Up Book; Learning Media; Teach English; Kindergarten; ADDIE Model